Diamond anvil cell using metallic diamond electrodes. (9th March 2017) - Matsumoto, Ryo; Irifune, Tetsuo; Tanaka, Masashi; Takeya, Hiroyuki; Takano, Yoshihiko
Abstract: A novel diamond anvil cell specialized for resistivity measurements under high pressure have been developed. Boron-doped metallic diamond electrodes were deposited onto a nano-polycrystalline diamond anvil using a microwave plasma-assisted chemical vapor deposition technique combined with electron beam lithography. The various designs of boron-doped metallic diamond electrodes were demonstrated, and they showed no signs of degradation after repeated compression.